2014
DOI: 10.1002/capr.12007
|View full text |Cite
|
Sign up to set email alerts
|

Training novice psychotherapists: Comparing undergraduate and graduate students' outcomes

Abstract: Aim: This paper describes and contrasts the impact of two 13-week counsellor training programmes in integrative-experiential psychotherapy; one with 24 undergraduate psychology students presented in this paper, and the other with archival data from Pascual-Leone and Andreescu's study of 22 clinical psychology graduate students. Method: The programmes taught psychotherapy to trainees who conducted single sessions with eight volunteers. Outcomes of these sessions were measured at four time points using both trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Most studies reported on descriptive data ( n = 2) or used qualitative analyses (e.g., grounded theory, consensual qualitative method, thematic analysis) of the data ( n = 5). Except for Pascual-Leone, Andreescu, and Yeryomenko (2015), all studies reported on original data sets. Pascual-Leone, Rodriguez-Rubio, and Metler (2013) reported on new data as well as previously published data (Pascual-Leone, Wolfe, & O’Connor, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies reported on descriptive data ( n = 2) or used qualitative analyses (e.g., grounded theory, consensual qualitative method, thematic analysis) of the data ( n = 5). Except for Pascual-Leone, Andreescu, and Yeryomenko (2015), all studies reported on original data sets. Pascual-Leone, Rodriguez-Rubio, and Metler (2013) reported on new data as well as previously published data (Pascual-Leone, Wolfe, & O’Connor, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…2 By adding the personal accounts of 21 graduate students, this study extended Pascual-Leone et al’s (2012) findings on 24 undergraduates’ experiences, raising the number of cases represented in the qualitative analysis to 45. In a later study, Pascual-Leone et al (2015) used quantitative analyses to examine this same group of undergraduates and graduate students in order to compare the change in standardized outcome measures reported by students and their clients over the time of training. Allen and colleagues (2000) also used a control group but compared their survey results with a control group of students in psychotherapy training that did not explicitly focus on integration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of findings from research on effectiveness training in psychotherapy are often challenging to understand due to their inherent limitations (e.g., difficulty implementing randomized clinical trials, influence and bias in interviewing for qualitative and survey studies, trainee-report of outcomes, retrospective studies). There is evidence that training and supervision can be effective for some outcomes, especially self-reported changes (e.g., Hill & Lent, 2006;Pascual-Leone et al, 2015;Smith & Trimble, 2016) and processbased variables (e.g., working alliance, helping skills; Hill et al, 2016). However, there is less evidence of the impact of training/supervision on client therapy outcomes (e.g., Erekson et al, 2017;Hill et al, 2016;Owen, Wampold, et al, 2016;Rousmaniere et al, 2016).…”
Section: Rationale For Using Technology In Trainingmentioning
confidence: 99%
“…Dentre os estudos de competência clínica, há aqueles que diferenciam duas classes de competências: técnicas e interpessoais (Pascual-Leone, Andreescu, & Yeryomenko, 2015)psychological or pedagogy studies are more effective and competent than other graduates. Research sample and methods: The sample included 235 psychotherapist-patient dyads, where psychotherapists where students of the Integrative Psychotherapy School.…”
Section: Introductionmentioning
confidence: 99%